A study of prevalence of anaemia in pregnant women among rural population in Rajasthan - Chaturvedi, Nidhi; Verma, Ashwani; Pratiksha; Chaudhary, Sakshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Anaemia in pregnancy is a major contributor in morbidity seen in pregnancy and childbirth. Prevalence of anaemia in India is still as high as 52%. Aim of the present study is to study the prevalence of anaemia and its socio demographic variables in rural population of Rajasthan. Methods: This study was done in our tertiary care teaching institute in obstetrics and gynecology department in Rajasthan. 2384 women who came to the ANC clinic were screened for anaemia. 1442 women found anemic were enrolled for study. They were interviewed through a structured questionnaire and data thus obtained was analyzed. Results: Prevalence of anaemia was found to be 60.4% in the study. Out of these 58.8% had mild anaemia, 39.8% had moderate anaemia, 1.04% severe anaemia and 0.2% had very severe anaemia. Maximum women were in the age group 20-24years (48.8%). A large proportion of women were from the lower socioeconomic strata 58.9%. Maximum anemic women had received primary education (63%), while 25% were illiterate and 12% received more than primary education. Prevalence of anaemia was almost similar in both primigravidas 49.1% and multigravidas 50.9%. Regular iron intake was seen in 56% women, 27.7% took iron folic acid (IFA) tablets but irregularly and 16.3% had not taken any supplements. Conclusions: Anaemia is still highly prevalent among pregnant women in rural Rajasthan. So, there is a need for effective implementation of the existing programmes for prevention and treatment of anaemia for healthy future generation.